2016
DOI: 10.1194/jlr.m066399
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in lipoprotein-associated apoC-III levels following volanesorsen therapy: phase 2 randomized trial results

Abstract: ApoC-III is a 79 amino acid glycoprotein synthesized principally in the liver and associated with apoB-containing lipoproteins and HDL ( 1 ). apoC-III plays a key role in determining serum triglyceride levels and is a potent inhibitor of both the LPL-dependent and -independent pathways of triglyceride-rich lipoprotein (TRL) clearance. Thus, apoC-III inhibits the apoC-II-mediated activation of LPL and also inhibits hepatic lipase that plays an important role in the conversion of dense VLDL to IDL. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 38 publications
4
48
1
Order By: Relevance
“…In patients with hypertriglyceridemia, including familial chylomicronemia syndrome (n = 3), volanesorsen monotherapy (n = 51), and as add-on to fibrate (n = 26), treated for 85 days resulted in a 82 ± 12% in apoB-apoC3, 81 ± 16% in Lp(a)-apoC3, and 81 ± 14% reduction in apoA1-apoC3 concentrations at day 92. Strong correlations were seen with these results and with total apoC3, chylomicron-apoC3, and VLDL-apoC3 [52].…”
Section: Asos To Apolipoprotein C-3supporting
confidence: 67%
“…In patients with hypertriglyceridemia, including familial chylomicronemia syndrome (n = 3), volanesorsen monotherapy (n = 51), and as add-on to fibrate (n = 26), treated for 85 days resulted in a 82 ± 12% in apoB-apoC3, 81 ± 16% in Lp(a)-apoC3, and 81 ± 14% reduction in apoA1-apoC3 concentrations at day 92. Strong correlations were seen with these results and with total apoC3, chylomicron-apoC3, and VLDL-apoC3 [52].…”
Section: Asos To Apolipoprotein C-3supporting
confidence: 67%
“…Specific target engagement in patients has been demonstrated for oligonucleotide therapeutics in cardiovascular diseases (54), viral infection (55), rare genetic diseases (56) and cancer (57). For the latter, safe and efficient tumor-selective drug delivery technology remains a key limitation.…”
Section: Discussionmentioning
confidence: 99%
“…A dose-dependent decrease in the plasma APOC3 levels was observed in volanesorsen-treated patients with an accompanying decrease in plasma TG levels ranging from 31.3% to 70.9% over the placebo group. Using a novel high-throughput chemiluminescent ELISA, authors reported a decrease in APOC3 associated with specific lipoproteins [135]. The therapy was generally well tolerated with no effects on renal or hepatic functions.…”
Section: Pharmacological Targeting Of Lplmentioning
confidence: 99%